Regulatory Mechanisms of Plant Growth-Promoting Rhizobacteria and Plant Nutrition against Abiotic Stresses in Brassicaceae Family - Jalal, Arshad [UNESP]; da Silva Oliveira, Carlos Eduardo [UNESP]; Galindo, Fernando Shintate [UNESP]; Rosa, Poliana Aparecida Leonel [UNESP]; Gato, Isabela Martins Bueno [UNESP]; de Lima, Bruno Horschut [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2023)
Extreme environmental conditions, such as abiotic stresses (drought, salinity, heat, chilling and intense light), offer great opportunities to study how different microorganisms and plant nutrition can influence plant growth and development. The intervention of biological agents such as plant growth-promoting rhizobacteria (PGPRs) coupled with proper plant nutrition can improve the agricultural importance of different plant species. Brassicaceae (Cruciferae) belongs to the monophyletic taxon and consists of around 338 genera and 3709 species worldwide. Brassicaceae is composed of several important species of economical, ornamental and food crops (vegetables, cooking oils, forage, condiments and industrial species). Sustainable production of Brassicas plants has been compromised over the years due to several abiotic stresses and the unbalanced utilization of chemical fertilizers and uncertified chemicals that ultimately affect the environment and human health. This chapter summarized the influence of PGPRs and nutrient management in the Brassicaceae family against abiotic stresses. The use of PGPRs contributed to combating climate-induced change/abiotic factors such as drought, soil and water salinization and heavy metal contamination that limits the general performance of plants. Brassica is widely utilized as an oil and vegetable crop and is harshly affected by abiotic stresses. Therefore, the use of PGPRs along with proper mineral nutrients management is a possible strategy to cope with abiotic stresses by improving biochemical, physiological and growth attributes and the production of brassica in an eco-friendly environment.
Keywords: abiotic stresses; Brassicaceae; microorganisms; nutrition; stressful conditions; sustainability